Adoption and usability of Artificial Intelligence in marketing content creation - Morales, Narcisa Medranda (Journal of Posthumanism, 2025)
This article aims to analyze the adoption and usability of Artificial Intelligence (AI) in digital marketing content creation, simultaneously addressing associated perceptions, challenges, and ethical considerations. A mixed methodology was developed using a descriptive-exploratory approach, applying a digital survey to 470 users and complemented by a focus group composed of six advertising agencies and company experts. The results indicate a high degree of adoption of AI-based tools, highlighting their ease of use and benefits in productivity, operational efficiency, and strategic optimization. At the ethical level, significant concerns about authorship, content originality, and potential algorithmic biases emerged. It is concluded that although AI is widely accepted in the sector, ethical and operational challenges remain. Ongoing technology training programs and the development of clear ethical guidelines are recommended to ensure these tools’ sustainable and responsible adoption in contemporary marketing.